Regional Differences in Carbon-14 Data of the 993 CE Cosmic Ray Event - Miyake, Fusa; Hakozaki, Masataka; Kimura, Katsuhiko; Tokanai, Fuyuki; Nakamura, Toshio; Takeyama, Mirei; Moriya, Toru (Frontiers in Astronomy and Space Sciences, 2022)
Cosmogenic nuclides such as 14C from tree rings and 10Be and 36Cl from ice cores are excellent proxies for the past extremely large solar energetic particle (SEP) events, which are dozens of times larger than the largest SEP event in the history of observation. So far, several rapid 14C increases have been discovered, which are considered to have originated from extreme SEP events (or set of successive SEP events) from verifications using multiple cosmogenic nuclide analyses in natural archives. Although these events are characterized by a rapid increase in cosmogenic nuclide concentrations, 14C data recorded worldwide do not always show similar variations, especially during the 993 CE event, where a rapid increase was recorded in either 992–993 CE or 993–994 CE in several records. We present new 14C data of the Japanese cedar sample for the 993 CE event. Although the latest data show no significant increase in one year, an overall increase pattern is consistent with the previous reported 14C data of the Japanese cedar, which supports that a significant 14C increase occurred from 993 to 994 CE in the Japanese sample. Given the dominant 14C production in high latitudes by SEPs, the difference in timing of increase may be a transport effect in the atmosphere. Moreover, the difference in the timing of the 14C increase can cause a 1-year age-determination error using the 993 CE radiocarbon spike. Compared with the 14C data between tree samples from high latitude and midlatitude, including Japan, high latitude data can capture 14C changes originating from SEP events more quickly and clearly and may be more suitable for a SEP event exploration in the past.